Early Detection and Intervention of Preschool-Aged Children Using Android-Based Monitoring during the COVID-19 Pandemic in Central Java - Triwiji Lestari; Elisa (Jurnal Keperawatan Indonesia, 2024)
Preschool age is widely recognized as a critical phase in child development, often referred to as the golden period, the window of opportunity, and the critical period. Alarming statistics from the Indonesian Ministry of Health reveal that 16% of Indonesian toddlers, amounting to 0.4 million children, experience developmental delays, encompassing fine and gross motor skills, hearing impairments, reduced cognitive abilities, and speech delays. This study aims to assess the effectiveness of an Android-based early detection and intervention system on the development of preschool children during the challenging circumstances of the COVID-19 pandemic in Central Java. The research employed a quasi-experimental design without a control group using a range of instruments, including observation sheets, the Sahabat Bunda application, the pre-screening developmental questionnaire (PDQ), and anthropometric measurements. Data analysis was conducted using the Wilcoxon test because the data were not normally distributed. The study’s results underscore a significant influence between the initial developmental status of children and their subsequent progress following developmental intervention, with a remarkable p-value of 0.001. In conclusion, this research demonstrates that providing developmental intervention positively impacts the overall development of preschool children. This study substantially benefits the community, specifically preschool-age children and their parents. The utilization of the Sahabat Bunda application emerges as a valuable tool for early detection of developmental issues and to foster the growth of preschool-age children. This research contributes to enhancing child development, particularly in the context of the COVID-19 pandemic. Keywords: android, early detection of development, preschool   Abstrak Deteksi dan Intervensi Dini Anak Usia Prasekolah Menggunakan Pemantauan Berbasis Android pada Masa Pandemi COVID-19 di Jawa Tengah. Usia prasekolah umumnya diakui sebagai fase kritis dalam perkembangan anak, sering disebut sebagai periode emas, jendela kesempatan, dan periode kritis. Data statistik yang dari Kementerian Kesehatan Indonesia mengungkapkan bahwa 16% dari anak-anak balita Indonesia, sekitar 0,4 juta anak, mengalami keterlambatan perkembangan, mencakup keterlambatan keterampilan motorik halus dan kasar, gangguan pendengaran, kemampuan kognitif yang berkurang, dan keterlambatan bicara. Penelitian ini bertujuan untuk menilai efektivitas sistem deteksi dini dan intervensi berbasis Android terhadap pertumbuhan dan perkembangan anak usia prasekolah selama situasi sulit pandemi COVID-19 di Jawa Tengah. Desain penelitian ini adalah quasi-experimental tanpa kelompok kontrol menggunakan berbagai alat, termasuk lembar observasi, aplikasi Sahabat Bunda, Pre-Screening Developmental Questionnaire (PDQ), dan pengukuran antropometri. Analisis data dilakukan menggunakan uji Wilcoxon dikarenakan data tidak terdistribusi secara normal. Hasil penelitian ini menunjukkan pengaruh signifikan antara status perkembangan awal anak-anak dan kemajuan mereka selama intervensi perkembangan, dengan nilai p 0,001. Secara keseluruhan, penelitian ini menunjukkan bahwa pemberian intervensi perkembangan berdampak positif pada perkembangan anak usia prasekolah. Penelitian ini sangat bermanfaat bagi masyarakat, khususnya anak-anak usia prasekolah dan orang tua mereka. Penggunaan aplikasi Sahabat Bunda muncul sebagai alat berharga untuk mendeteksi dini masalah perkembangan dan memfasilitasi pertumbuhan anak-anak usia prasekolah. Penelitian ini berkontribusi pada peningkatan perkembangan anak, terutama dalam konteks pandemi COVID-19. Kata Kunci: android, deteksi dini perkembangan, prasekolah